2005
DOI: 10.1091/mbc.e04-09-0784
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Radial Spoke Subcomplex Containing Radial Spoke Protein 3 and Heat Shock Protein 40 in Sperm Flagella of the AscidianCiona intestinalis

Abstract: Members of the heat-shock protein (HSP)40 regulate the protein folding activity of HSP70 proteins and help the functional specialization of this molecular chaperone system in various types of cellular events. We have recently identified Hsp40 as a component of flagellar axoneme in the ascidian Ciona intestinalis, suggesting a correlation between Hsp40 related chaperone system and flagellar function. In this study, we have found that Ciona 37-kDa Hsp40 is extracted from KCl-treated axonemes with 0.5 M KI soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…ciency with instability of ciliary tubulin, we examined expression of Hsps, products of major HSF1-target genes. In addition to the TCP-1 complex, Hsps such as Hsp70, Hsp90, and Hsp40 are distributed in the cilia and are related to axonemal protein turnover (47)(48)(49)(50). Immunohistochemical study showed that major cytoplasmic Hsps such as Hsp110, Hsp90, Hsp70, Hsp40, and Hsp27 were localized both in the cilia and in the cytoplasm of the nasal respiratory epithelium (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…ciency with instability of ciliary tubulin, we examined expression of Hsps, products of major HSF1-target genes. In addition to the TCP-1 complex, Hsps such as Hsp70, Hsp90, and Hsp40 are distributed in the cilia and are related to axonemal protein turnover (47)(48)(49)(50). Immunohistochemical study showed that major cytoplasmic Hsps such as Hsp110, Hsp90, Hsp70, Hsp40, and Hsp27 were localized both in the cilia and in the cytoplasm of the nasal respiratory epithelium (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the folding and assembly of tubulin is facilitated by Hsps such as Hsp70, Hsp90, and TCP-1 (46), and Hsp40, a component of the radial spoke complex (48,49), is induced during cilium regeneration (60). These observations suggest that Hsps are required for formation and function of cilia.…”
Section: Discussionmentioning
confidence: 99%
“…Mutant form of Cu/Zn SOD has previously been reported to interact with heat-shock protein (HSP) 70 and HSP40, and B-crystallin (Shinder et al, 2001). Several studies have shown that flagella and cilia contain HSP70 (Bloch and Johnson, 1995;Stephens, 1997;Williams and Nelsen, 1997;Stephens and Lemieux, 1999), HSP90 (Williams and Nelsen, 1997;Stephens and Lemieux, 1999) and HSP40 (Satouh et al, 2005;Yang et al, 2005;Yang et al, 2008). Furthermore, flagellar motility is affected by the redox-dependent regulation of the outer dynein arms (Wakabayashi and King, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences in phosphorylation between FWT and SWT sperm are potentially associated with differences in nitration. As well as being linked to nitration Ischiropoulos et al, 1992;Lymar et al, 1996;Crow et al, 1997), SOD interacts latently with HSPs (Shinder et al, 2001), which consist of a radial spoke and central pair system that may regulate dynein activity (Bloch and Johnson, 1995;Stephens, 1997;Williams and Nelsen, 1997;Satouh et al, 2005;Yang et al, 2005;Yang et al, 2008). Thus, SOD may play an important role in the regulation of sperm motility by reducing ONOO -formation or nitration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation